Relationship Between Perception of Dental and Smile Aesthetics and Adolescent Self-Confidence in Jakarta - Delima, Anita Rosa; Maheswari, Rifda Zhafira; Solachuddin, Ar Razi Ryoshi; Siregar, Fazwishni (YARSI Dental Journal, 2025)
Introduction: Adolescents are unique individuals who go through different phases of psychological development and identity from childhood to adulthood. In this period, adolescents have an important part in their lives, namely self-confidence. This can be seen when the teenager begins to pay attention to the condition of his teeth and smile. Objectives: This research was conducted to examine the relationship between the perception of the aesthetics of teeth and smile with the self-confidence of adolescents in Jakarta by using a random sampling research method. Material and Methods: This research is quantitative with a cross-sectional study. Results: The results indicate that there are still many teenagers in Jakarta who feel less confident about the aesthetics of their teeth and smile. Discussion: A significant positive correlation was found between perception of dental and smile aesthetics and adolescent self-confidence, with females showing greater concern for appearance. Conclusion: It can be concluded that the perception of the aesthetics of teeth and smile affects the self-confidence of the teenager.